The Influence of Leadership and Business Strategy on The Competitive Advantage of Millennial Small Entrepreneurs in Medan City - Ritha F. Dalimunthe; Magdalena Linda Leonita Sibarani (PT Inovasi Pratama Internasional, 2025)
Millennial small entrepreneurs engaged in the culinary field are considered to be a generation that is actively working, innovative because they use digitalization, and have self-confidence and have a strong will to work. There is a difference between the millennial generation and the previous generation, namely the baby boom generation who were born in the 60-70s era. Therefore, there is a need for research on millennial small entrepreneur leadership. Small entrepreneurs have not entirely used information technology optimally (Dalimunthe, 2019). Therefore, it is necessary to conduct research on leadership and business strategies against the competitive advantage of millennial small entrepreneurs in Medan City. The results of research on the competitiveness of a small business company are the strengths that must exist for a company, namely the human resources who run the business so that their products can be superior and accepted by the market Dalimunthe (2018). The research objective is to analyze and explain the competitive advantages of a small business product which is the key to success in a product of millennial small entrepreneurs. Therefore, in this study, the researcher wants to conduct further research on discussing the factors that influence the competitive advantage of small business products born from the millennial generation (generation y) in Medan City. The results of research in 2016 were to have an entrepreneurial mindset for a small entrepreneur so that aspects of internal control are needed as well as challenges or obstacles which are lessons for business development. To see the entrepreneurial mindset in small businesses, this research is seen from the aspects of the characteristics of millennial leadership as well as from the aspect of business strategies seen from the product and product value and online marketing.